Clinical and polysomnographic predictors of laryngopharyngeal reflux in obstructive sleep apnea syndrome - Caparroz,Fábio Azevedo (2019)
Abstract Introduction Obstructive sleep apnea syndrome and laryngopharyngeal reflux are diseases with a high prevalence in the overall population; however, it remains unclear whether they are diseases with the same risk factors present in the same populations or if there is any association between them. Objectives To evaluate and determine the prevalence of laryngopharyngeal reflux in patients with moderate and severe obstructive apnea syndrome and also to determine its predictive factors. Methods Historical cohort, cross-sectional study of patients aged 18-70 years, referred to a tertiary service Otorhinolaryngology outpatient clinic with a polysomnographic diagnosis of moderate or severe obstructive sleep apnea syndrome. The reflux symptom index questionnaire and the reflux finding score at indirect videolaryngoscopy were applied to the assessed population, considering the inclusion and exclusion criteria. Results Fifty-six patients were evaluated, of which 64.3% had a positive laryngopharyngeal reflux (positive reflux symptom index and/or positive endolaryngeal reflux finding score). Body mass index was a predictor of reflux presence in this group of patients with moderate to severe obstructive sleep apnea syndrome. In patients with positive score for endoscopic findings and reflux symptom index (12.3%), there was a trend toward significance for a higher mean apnea-hypopnea index and a higher percentage of sleep time with oxyhemoglobin saturation below 90% (p = 0.05). Conclusion The prevalence of laryngopharyngeal reflux was higher in this group of patients with moderate to severe obstructive sleep apnea syndrome, and the body mass index was a predictor of laryngopharyngeal reflux in these patients. There was a trend toward greater oxyhemoglobin desaturation in patients with a positive score for reflux symptoms index (RSI) and reflux finding score (RFS).